FRI0405 CARTILAGE BIOMARKERS S-COLL2-1 AND S-COLL2-1NO2 ARE HELPFUL IN IDENTIFYING KNEE OSTEOARTHRITIS PATIENTS AT RISK OF DISEASE WORSENING. (2nd June 2020) - Henrotin, Y.; Costes, B.; Malaise, M.; Loeuille, D.; Conrozier, T.; Maugars, Y.; Pelousse, F.; Lemaire, J. M.; Helleputte, T.; Tits, C.; Cobraiville, E.; Pirson, S.; et al.
Abstract : Background: Coll2-1 is a peptide of 9 amino acid located in the triple helix of type II collagen molecule reflecting cartilage degradation (1). Coll2-1NO2 is the nitrated form of Coll2-1 and considered as a biomarker of the inflammatory-related cartilage degradation (2). This peptide is involved in osteoarthritis physiopathology since it was demonstrated that Coll2-1 induced synovitis in rat. Objectives: To identify if biochemical markers s-Coll2-1 and s-Coll2-1NO2 are associated to knee osteoarthritis (OA), focusing on pain, function as well as structural features assessed by MRI in various knee compartments and to assess their ability at predicting knee OA worsening. Methods: 116 subjects with knee OA were followed during one year with pain, function and MRI evaluation (PRODIGE study, NCT02070224 ). Type II collagen-specific biomarker Coll2-1 and its nitrated form Coll2-1NO2 were directly measured in serum using immunoassays at baseline and after three, six and twelve months follow-up. Results: sColl2-1 and sColl2-1NO2 were associated to several baseline knee features quantified with Whole-Organ Magnetic Resonance Imaging Score (WORMS). S-Coll2-1 was significantly correlated with bursitis (r=0.29, P<0.01), bone attrition (r=0.25, P=0.01), cysts (r=0.24, P=0.02) and cartilage (r=0.23, P=0.03) WORMS sub-scores for the whole joint as well as with the medial femorotibial joint sum score (r=0.26, P=0.01) and medial femorotibial joint cartilage (r=0.23, P=0.02). s-Coll2-1NO2 was correlated with WORMS total score (r=0.23, P=0.02), WORMS scores in the patellofemoral (r=0.23, P=0.02) and medial femorotibial compartments (r=0.21, P=0.03) and with osteophytes scores (r=0.27, P<0.01). Baseline s-Coll2-1NO2 was higher in subjects with a pain worsening (426.4 pg/mL [278.04-566.95]) as compared to non-progressors (306.84 [200.37-427.84]) over one year (AUC=0.655, P=0.015). Conclusion: Cartilage biomarkers s-Coll2-1 and s-Coll2-1NO2 are associated to several knee OA features quantified with WORMS scoring system on MRI. Serum values of Coll2-1NO2 are also associated to a worsening of target knee pain over one year. Coll2-1 and Coll2-1NO2, in association with other structural features, pain and function, could help at identifying OA phenotypes and patients at risk of OA worsening. References: [1]Mobasheri A, Lambert C, Henrotin Y. Coll2-1 and Coll2-1NO2 as exemplars of collagen extracellular matrix turnover - biomarkers to facilitate the treatment of osteoarthritis? Expert Rev Mol Diagn. 2019 Sep;19(9):803-812. doi: 10.1080/14737159.2019.1646641. Epub 2019 Sep 4. [2]Lambert C, Borderie D, Dubuc JE, Rannou F, Henrotin Y. Type II collagen peptide Coll2-1 is an actor of synovitis. Osteoarthritis Cartilage. 2019 Nov;27(11):1680-1691. doi: 10.1016/j.joca.2019.07.009. Epub 2019 Jul 17. Acknowledgments: PRODIGE study (NCT02070224 ) was performed in the framework of a convention between the Walloon region and ARTIALIS SA. (convention n°6905). Disclosure of Interests: Yves Henrotin Grant/research support from: HEEL, TILMAN, Berenice Costes Employee of: Artialis SA, Michel Malaise: None declared, Damien Loeuille: None declared, Thierry Conrozier Consultant of: LABRHA, SANOFI, MEDAC, Yves Maugars: None declared, Franz Pelousse Shareholder of: Sodiray, Jean-Marc Lemaire Shareholder of: Sodiray, Thibault Helleputte Shareholder of: DNAlytics, Cedric Tits Employee of: DNAlytics, Elisabeth Cobraiville Employee of: Artialis SA, Sebastien Pirson Employee of: Artialis, Laetitia Garcia Employee of: Artialis, Alain Labasse Employee of: Artialis SA, Anne-Christine Hick Employee of: Artialis SA